2015
DOI: 10.1139/cjz-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal oxidative capacity of skeletal muscles in hibernating Daurian ground squirrels (Spermophilus dauricus)

Abstract: We investigated the mechanism of high oxidative capacity of skeletal muscles in hibernating Daurian ground squirrels (Spermophilus dauricus Brandt, 1843). Myoglobin (Mb) levels, as well as citrate synthase and lactate dehydrogenase (LDH) activities, were measured by spectrophotometry. Mb content in the soleus (SOL) muscle lasted from the beginning of hibernation to spring. Mb content in SOL was 87% higher in the hibernating group than in the summer group. Mb content in the extensor digitorum longus (EDL) muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Due to fact that small mammals undergo torpor‐arousal cycle during hibernation, increased expression of ATP synthase suggests higher ATP production, which makes sense when rapid muscle activation is needed in critical situations. Our previous study on citrate synthase activity also showed that the activity of both slow SOL and fast EDL muscles in hibernating Daurian ground squirrels were no less than pre‐hibernation (Jiang et al, ). This also indicates that the mitochondrial aerobic oxidation and energy production capacity of skeletal muscle in hibernating ground squirrels are well preserved.…”
Section: Discussionmentioning
confidence: 87%
“…Due to fact that small mammals undergo torpor‐arousal cycle during hibernation, increased expression of ATP synthase suggests higher ATP production, which makes sense when rapid muscle activation is needed in critical situations. Our previous study on citrate synthase activity also showed that the activity of both slow SOL and fast EDL muscles in hibernating Daurian ground squirrels were no less than pre‐hibernation (Jiang et al, ). This also indicates that the mitochondrial aerobic oxidation and energy production capacity of skeletal muscle in hibernating ground squirrels are well preserved.…”
Section: Discussionmentioning
confidence: 87%
“…Daurian ground squirrels (Spermophilus dauricus (Brandt, 1843)) are native to the dry plain steppes and deserts of North-Eastern China and Eastern Mongolia (Shar and Lkhagvasuren 2008;Jiang et al 2015). These rodents reach maturity at the age of 2-years and enter hibernation at the end of May while younger ground squirrels may be active until autumn (Shar and Lkhagvasuren 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While most mammals experience muscle atrophy during hibernation, ground squirrels show little muscle atrophy during prolonged periods of skeletal muscle disuse during hibernation, which suggests that they have developed adaptive mechanisms to preserve skeletal muscle mass (Jiang et al 2015). While most mammals experience muscle atrophy during hibernation, ground squirrels show little muscle atrophy during prolonged periods of skeletal muscle disuse during hibernation, which suggests that they have developed adaptive mechanisms to preserve skeletal muscle mass (Jiang et al 2015).…”
Section: Introductionmentioning
confidence: 99%